RELATIONSHIP BETWEEN BREAST CARE HISTORY DURING PREGNANCY AND COLOSTRUM VOLUME IN 2–6 HOURS POSTPARTUM MOTHERS - Husniyati Sajalia; Anatun Aupia; Novi Paramitasari MS (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Colostrum is the first breast milk produced and plays a crucial role in protecting the newborn's immune system. However, in some postpartum mothers, colostrum production in the early hours after delivery is not optimal. One measure thought to play a role in increasing lactation readiness is breast care during pregnancy. Quantitative evidence directly linking antenatal breast care to colostrum volume in the early hours postpartum is limited. Objectives: To determine the relationship between breast care history during pregnancy and colostrum volume in postpartum mothers 2–6 hours. Methods: This quantitative study used a cross-sectional design in 30 mothers 2–6 hours postpartum, selected using total sampling. Breast care history was collected through a structured questionnaire, while colostrum volume was measured directly using manual pumping and a measuring cup (mL). Data analysis was performed using the Mann–Whitney test. Results: Mothers with a history of breast care during pregnancy had significantly higher colostrum volumes than mothers without breast care (U=33.50; Z=-3.07; p=0.002). This difference in median colostrum volumes suggests clinical significance in supporting early breastfeeding initiation in the early postpartum hours. Conclusion: Breast care history during pregnancy is significantly associated with colostrum volume in mothers 2–6 hours postpartum. Integrating breast care education and practices into antenatal care has the potential to support early breastfeeding success.